Gestational and early postnatal hypothyroidism alters VGluT1 and VGAT bouton distribution in the neocortex and hippocampus, and behavior in rats - Navarro, Daniela; Alvarado, Mayvi; Navarrete, Francisco; Giner, Manuel; Obregon, Maria Jesus; Manzanares, Jorge; Berbel, Pere (Frontiers in Neuroanatomy, 2015)
Thyroid hormones are fundamental for the expression of genes involved in the development of the CNS and their deficiency is associated with a wide spectrum of neurological diseases including mental retardation, attention deficit-hyperactivity disorder and autism spectrum disorders. We examined in rat whether developmental and early postnatal hypothyroidism affects the distribution of vesicular glutamate transporter-1 (VGluT1; glutamatergic) and vesicular inhibitory amino acid transporter (VGAT; GABAergic) immunoreactive (ir) boutons in the hippocampus and somatosensory cortex, and the behavior of the pups. Hypothyroidism was induced by adding 0.02% methimazole (MMI) and 1% KClO4 to the drinking water starting at embryonic day 10 (E10; developmental hypothyroidism) and E21 (early postnatal hypothyroidism) until day of sacrifice at postnatal day 50. Behavior was studied using the acoustic prepulse inhibition (somatosensory attention) and the elevated plus-maze (anxiety-like assessment) tests. The distribution, density and size of VGlut1-ir and VGAT-ir boutons in the hippocampus and somatosensory cortex was abnormal in MMI pups and these changes correlate with behavioral changes, as prepulse inhibition of the startle response amplitude was reduced, and the percentage of time spent in open arms increased. In conclusion, both developmental and early postnatal hypothyroidism significantly decreases the ratio of GABAergic to glutamatergic boutons in dentate gyrus leading to an abnormal flow of information to the hippocampus and infragranular layers of the somatosensory cortex, and alter behavior in rats. Our data show cytoarchitectonic alterations in the basic excitatory hippocampal loop, and in local inhibitory circuits of the somatosensory cortex and hippocampus that might contribute to the delayed neurocognitive outcome observed in thyroid hormone deficient children born in iodine deficient areas, or suffering from congenital hypothyroidism.